Pengaruh Dimensi Budaya Nasional Hofstede terhadap Kinerja Pegawai dalam Pengelolaan Keuangan di Pemerintah Kota Kupang - Molle, Sarah Suenita; Man, Stanis; Sonbay, Yolinda Yanti; Perseveranda, M. E.; Adrianus, Jou Sewa (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The purpose of this research is to determine the influence of Hofstede's national cultural dimensions in the form of power distance, collectivism, uncertainty avoidance, feminism, and long term organization on employee performance in financial management in the Kupang City Government. This type of research is based on the characteristics of the research variables using survey research. By using a correlative associative quantitative approach (causal/cause and effect). The research results show that the variables power distance, individualism, masculinity, long term organization have a positive and significant effect on employee performance in financial management. Meanwhile, the uncertainty advoidance variable has a positive and insignificant effect on employee performance in financial management in the Kupang City Government.